Anteseden Kepuasan Berdampak Pada Loyalitas Pelanggan - Bagus Arya Wijaya; Sang Ayu Nyoman Jesi Yanti; I Gusti Putu Agung Widya Goca; I Dewa Agung Ayu Eka Idayanti; Tiarto (Jurnal Ekonomi, 2024)
The research aims to analyze the antecedents of satisfaction that impact customer loyalty. Using a purposive sampling method to determine a sample of 100 customers. This research uses quantitative methods. Data were analyzed using Smart PLS: outer model analysis, inner model, and hypothesis testing. The results show that there is no influence of service quality on satisfaction, there is an influence of complaint handling on satisfaction, there is no influence of satisfaction on customer loyalty, there is an influence of Service Quality on Loyalty, there is no influence of complaint handling on customer loyalty, there is no influence of satisfaction on customer loyalty. In this research, satisfaction cannot mediate the relationship between service quality and customer loyalty and there is no indirect influence of the complaint handling variable on customer loyalty through satisfaction. In this research, satisfaction cannot mediate the relationship between complaint handling and customer loyalty.